Nordic Mediation Research (Springer International Publishing, 2018)
This open access book presents twelve unique studies on mediation from researchers in Denmark, Finland, Norway and Sweden, respectively. Each study highlights important aspects of mediation, including the role of children in family mediation, the evolution and ambivalent application of restorative justice in the Nordic countries, the confusion of roles in court-connected mediation, and the challenges in dispute systems. Over the past 20-30 years, mediation has gained in popularity in many countries around the world and is often heralded as a suitable and cost-effective mode of conflict resolution. However, as the studies in this volumes show, mediation also has a number of potential drawbacks. Parties' self-determination may be jeopardized, affected third parties are involved in an inadequate way, and the legal regulations may be flawed. The publication can inspire research, help professionals and policymakers in the field and be used as a textbook.